Change in Pulse Wave Velocity and Short‐Term Development of Cardiovascular Events in the Hemodialysis Population - Bahous, Sola Aoun (2016)
The association between single measurements of carotid‐femoral pulse wave velocity (cfPWV) and cardiovascular (CV) events is driven by late events beyond 12 months of follow‐up. This prospective study compares single measurements of cfPWV vs the 2‐year delta cfPWV and the association with short‐term development of CV events in hemodialysis patients. cfPWV was performed at t=0 and t=1 two years later, and patients were followed‐up for development of CV events through 12 months (n=66). In Cox regression models adjusted for CV risk factors, history of CV events and delta cfPWV remained associated with the development of CV events (hazard ratio for prior CV events=8.9, P=.03; hazard ratio for delta cfPWV=1.14; P=.002). When delta cfPWV was substituted for single cfPWV measurement, none of the single measures were associated with new CV events. The change in cfPWV, but not single measurements of cfPWV, was associated with the development of CV events through 12 months.